PENGARUH WAKTU INOKULASI Trichoderma spp. DAN Glomus sp. TERHADAP PERTUMBUHAN SEMAI AKASIA (Acacia mangium) - Setyaningrum, Prastuti M; Suryantini, Rosa; Wulandari, Reine Suci (Universitas Tanjungpura, 2017)
Acacia (Acacia mangium) is a plant spesies which can grow rapidly despite living on marginal land. One effort that can be done is by adding biological agents, for example Trichoderma and Glomus sp. The purpose of this research was to uncover the best inoculation time of Trichoderma and Glomus sp. to the growth of acacia. The research consisted of 14 treatments, involving : W0 : Control; W1: Trichoderma sp. 1 three days before Glomus sp.; W2: Trichoderma sp. 1 together Glomus sp.; W3: Trichoderma sp. 1 seven days after Glomus sp.; Â W4: Trichoderma sp. 2 three days before Glomus sp.; W5: Trichoderma sp. 2 together Glomus sp.; W6: Inoculation with Trichoderma sp. 2 seven days after Glomus sp.; Â W7: Trichoderma sp. 3 three days before Glomus sp.; W8: Trichoderma sp. 3 together Glomus sp.; W9: Trichoderma sp. 3 seven days after Glomus sp. These treatments were repeated for three times until 30 exprerimental units were gathered. The research was designed based on a completely ramdomised design. The data were observed for 2 months including the data about diameter and height. Result of the observation was analysed quantitatively using ANOVA. It was then continued by Honestly Significant Difference (HSD) test. The result indicated that providing Trichoderma sp. 3 three days before Glomus sp. (W7) did not give a significant increase in height. Meanwhile, inoculation Trichoderma sp. 1 together with Glomus sp. (W2) yielded a significant value for the increase in diameter. Finally, it is hoped that results of this research can be used and applied on other forest plants such as Pinus. Keyword : Acacia, Diameter, Glomus, Height, Trichoderma